Capabilities of Rice Processors: Issues for Competitiveness of Rice in Enugu State, Nigeria - Cynthia Ebere Nwobodo; Celestina Dupe Innih; Mabel Ukamaka Dimelu; Jane Mbolle Chah (Journal of Agricultural Extension)
The study was conducted to assess the technological capability of processors in Enugu State, Nigeria. Multi-stage sampling procedure was used in selecting 120 respondents across two communities in two local government of agricultural zones selected.  Frequencies and percentages were used to analyse the data collected. Findings showed that 88.3% parboilers were aware of maintaining hygienic conditions and 58.3% practice. While 100.0% know that they should wash/dewater paddy till wash water is colourless, but only 33.3% practiced. The majority (80.0%)of miller know that  operational cost is reduced by ensuring that paddy is at 1%impurity rate but only 20.0% practiced. Only 15% millers owned de-stoning machine and offered the service. A minority (31.7%) of millers package milled rice while only 1.7% practiced size sorting, buffering and polishing of milled rice. This implied  that rice processing in Enugu State is at primary processing of parboiling, drying, milling and bagging. Revealing the  need or training and capacity building on value addition processing such as de-stoning, size sorting, polishing, and buffering which will place domestic rice at par with foreign rice. The reasons for the high disparity between knowledge and practice is a gap for extension workers to explore and address.